"The Extreme Male Brain?" Incrementum and the Rhetorical Gendering of Autism - Jordynn Jack (Disability Studies Quarterly, 2011)
The rhetorical figure of the incrementum, or scale, can help to account for how autism spectrum disorders (ASD) have been gendered as male, especially in Simon Baron-Cohen’s "Extreme Male Brain" theory. The incrementum occurs when female, male, and autistic brains are placed along a scale according to systemizing and empathizing abilities. This double hierarchy reinforces popular beliefs about sex and gender, drawing on the cultural resources of hi-tech culture, the service economy, and geekiness. In so doing, these theories overlook other important aspects of ASD, including alternative theories, the presence of autistic women and girls, and the needs and interests of autistic people themselves.
Keywords: Autism; gender; masculinity; rhetoric; technology